Antenatal determinants of maternal weight gain during pregnancy in nulliparous women of urban and suburban parts of Maharashtra - Dahake, Swati T.; Shaikh, Uzma (International Journal Of Community Medicine And Public Health, 2020)
Background: Weight gain in pregnancy remains a matter of great concern for women and health care providers. Adherence to a balanced diet throughout pregnancy, influences maternal body weight as well as short- and long-term health of mother and child. Objective of this study was to study antenatal maternal and social factors affecting maternal weight gain among Nulliparous women. Methods: study was carried out in antenatal clinics of tertiary care hospital and a suburban health center with sample size 197 and 97 respectively. Maternal weight was measured at the first antenatal clinic visit and at delivery. Statistical analysis was done with SPSS version 20. Statistical tests used were mean, percentages and chi square. Results: The antenatal determinants of maternal weight gain were: being underweight at the booking visit, maternal complications during pregnancy, passive cigarette smoking during third trimester, low educational level and low per capita income, controlling for the effect of gestational age. Conclusions: maternal educational level, per capital income, passive smoking, caloric and protein deficiency, early pregnancy body mass index determines the weight gain during pregnancy.